1991
DOI: 10.1007/bf01314326
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of BPV-like DNA in equine sarcoids

Abstract: The DNA from equine sarcoid samples from New York State and Switzerland was isolated and probed with bovine papillomavirus type 1 (BPV-1) to determine if BPV genomes were present. Twelve of 13 sarcoids from New York State and 17/20 sarcoids from Switzerland contained DNA that hybridized to the BPV-1 probe. Restriction enzyme analysis of the positive samples demonstrated restriction fragment profiles characteristic of BPV-1 in 22 sarcoids and restriction fragment profiles characteristic of bovine papillomavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 25 publications
6
66
1
Order By: Relevance
“…BPV DNA has not been detected in samples obtained from horses without sarcoids or in non-sarcoid equine tumours or equine papillomas (Otten et al, 1993;Nasir et al, 1997;Carr et al, 2001a, b). However, it has been found in some cases of dermatitis and the significance of this is as yet unknown (Angelos et al, 1991;unpublished observations). Despite the consistent finding of papillomavirus DNA in the sarcoid lesions, papillomavirus particles have not been demonstrated and the disease is, therefore, considered to be a non-productive infection in which viral DNA exists episomally (Amtmann et al, 1980;Lancaster, 1981).…”
Section: Bpv As the Causative Agent Of Sarcoidsmentioning
confidence: 97%
See 1 more Smart Citation
“…BPV DNA has not been detected in samples obtained from horses without sarcoids or in non-sarcoid equine tumours or equine papillomas (Otten et al, 1993;Nasir et al, 1997;Carr et al, 2001a, b). However, it has been found in some cases of dermatitis and the significance of this is as yet unknown (Angelos et al, 1991;unpublished observations). Despite the consistent finding of papillomavirus DNA in the sarcoid lesions, papillomavirus particles have not been demonstrated and the disease is, therefore, considered to be a non-productive infection in which viral DNA exists episomally (Amtmann et al, 1980;Lancaster, 1981).…”
Section: Bpv As the Causative Agent Of Sarcoidsmentioning
confidence: 97%
“…Since the initial suggestion of such a relationship between BPV and equine sarcoids by Olson & Cook (1951), groups in the USA, Australia, continental Europe and the UK have reported the presence of the closely related viruses BPV types 1 and 2 in equine sarcoids. Early studies detected BPV DNA in sarcoids from horses and donkeys using DNA hybridization techniques (Lancaster et al, 1979;Amtmann et al, 1980;Trenfield et al, 1985;Angelos et al, 1991;Lory et al, 1993;Reid et al, 1994). In more recent years, PCRbased detection methods offering greater sensitivity have been used to demonstrate the presence of BPV DNA in sarcoids.…”
Section: Bpv As the Causative Agent Of Sarcoidsmentioning
confidence: 99%
“…However, some studies have found BPV DNA in the skin of a small number of horses with nonsarcoid-related inflammatory skin conditions, but the significance of such a finding is unknown. 2,12,29 The frequency with which BPV can be detected in nonsarcoid skin conditions has not been determined in a larger sample of equine tissues. In addition, it is unclear where BPV is located histologically in these biopsies from unaffected horses.…”
Section: Introductionmentioning
confidence: 99%
“…26,29,34 In subsequent work, Southern blots were used to identify BPV1 or BPV2 genome(s) within tumor tissue, 1,2,19,38 and polymerase chain reaction (PCR)-based surveys routinely demonstrate that up to 100% of sarcoids contain BPV DNA. [12][13][14]23,24,27,38,39 A limited number of studies have been designed to investigate the role of BPV in cellular transformation in equine tissue.…”
mentioning
confidence: 99%